2006
DOI: 10.1080/15419060600631839
|View full text |Cite
|
Sign up to set email alerts
|

DE-Cadherin, a Core Component of the Adherens Junction Complex Modifies Subcellular Localization of theDrosophilaGap Junction Protein Innexin2

Abstract: The Drosophila innexin multigene family of gap junction encoding proteins consists of eight family members whose function in epithelial morphogenesis is mostly unknown. We have recently shown that innexin2 plays a crucial role in the organization of embryonic epithelia. Innexin2 protein accumulates in the epidermis in the apico-lateral membrane domain and colocalizes with core proteins of adherens junctions, such as DE-cadherin and Armadillo, the β-catenin homolog. Innexin2 localization is altered in both arma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…This finding is in line to the reported interaction between Inx2 and DE-cadherin in epidermis of early embryos [45]. To assess whether DE-cadherin and Inx2 also interact during dorsal closure stages, we monitored Inx2 protein levels in shotgun homozygous embryos and found that its protein levels at the plasma membrane are very reduced (Figure 6D, D'), indicating that DE-cadherin is required for Inx2 maintenance.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line to the reported interaction between Inx2 and DE-cadherin in epidermis of early embryos [45]. To assess whether DE-cadherin and Inx2 also interact during dorsal closure stages, we monitored Inx2 protein levels in shotgun homozygous embryos and found that its protein levels at the plasma membrane are very reduced (Figure 6D, D'), indicating that DE-cadherin is required for Inx2 maintenance.…”
Section: Resultssupporting
confidence: 89%
“…Given the known genetic interactions between Inx3 and other junction proteins [35], [45], the dorsal closure defects described above seemed unlikely to be due to the sole absence of zygotic Inx3 protein. We therefore examined whether loss of Inx3 might impinge on the localisation of Inx1, Inx2 and DE-cadherin in embryos at stages of dorsal closure by assessing the localization of these three proteins in Df-Inx3 homozygous embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Dm ‐Inx2 is required for embryonic gut formation [42], acting downstream of Wingless signaling [42,48]; Dm ‐Inx2 activity upstream of wingless , hedgehog , and the Notch ligand, delta , is a rare demonstration in insects of the interdependence of paracrine and gap junction communication [48]. Dm ‐Inx2 also was demonstrated to interact with adherens and septate junction proteins [43] and Dm ‐Inx3 [45], reciprocally affecting junctional distributions; specifically, it appears that D E‐Cadherin plays a role in proper trafficking of Dm ‐Inx2 channels [49]. Outside of embryonic development, Dm ‐Inx2, as noted above, interacts with Ogre in larval CNS glial cells, and knockdown results in reduced size of larval CNS and failure of flies to eclose (i.e., adults to emerge from pupa) [39]; the authors suggest this may occur due to a requirement for gap junctional communication between glial cells, and/or between glial cells and neurons.…”
Section: Roles Associated With Specific Innexinsmentioning
confidence: 99%
“…Primary antibodies used were: rabbit polyclonal a-htsM 1:500 , mouse monoclonal a-DE-cadherin 1:20 (Developmental Studies Hybridoma Bank), rabbit polyclonal anti-Innexin-1 1:100 (Bauer et al, 2006), rabbit polyclonal anti-Centrosomin 1:500 (Heuer et al, 1995), rabbit polyclonal anti-Phospho histone H3 1:1000 (Upstate Signaling). Secondary antibodies conjugated to Alexa Fluor 488, 568 or 633 were used at 1:500 (Molecular Probes).…”
Section: Immunofluorescencementioning
confidence: 99%